Recent advances in catalytic and non-catalytic epoxidation of terpenes: a pathway to bio-based polymers from waste biomass - Gunam Resul, Mohamad Faiz Mukhtar; Abdul Rehman, .; Saleem, Faisal; Usman, Muhammd; Lopez Fernandez, Ana María; Eze, Valentine C.; Harvey, Adam P. (Royal Society of Chemistry, 2023)
Epoxides derived from waste biomass are a promising avenue for the production of bio-based polymers, including polyamides, polyesters, polyurethanes, and polycarbonates. This review article explores recent efforts to develop both catalytic and non-catalytic processes for the epoxidation of terpene, employing a variety of oxidizing agents and techniques for process intensification. Experimental investigations into the epoxidation of limonene have shown that these methods can be extended to other terpenes. To optimize the epoxidation of bio-based terpene, there is a need to develop continuous processes that address limitations in mass and heat transfer. This review discusses flow chemistry and innovative reactor designs as part of a multi-scale approach aimed at industrial transformation. These methods facilitate continuous processing, improve mixing, and either eliminate or reduce the need for solvents by enhancing heat transfer capabilities. Overall, the objective of this review is to contribute to the development of commercially viable processes for producing bio-based epoxides from waste biomass.